An obligation to remedy damage in connection with an early release on licence - Muszyńska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The author presents doubts concerning interpretation of numerous legal grounds for remedying damage caused by an offence in the field of criminal law, including imposition of an obligation to remedy damage in connection with early release on licence. Emphasis is placed on problems with their application in judicial practice. The author in principle views the amendments in the scope of compensatory measures as positive, however, she considers the possibility of further amendments, which would lead to more rational legislative solutions.
Keywords: naprawa szkód; odszkodowanie; środek wyrównawczy; przestępca; pokrzywdzony